Keberkesanan strategi pentaksiran formatif terhadap pencapaian Geografi dan Matematik dalam kalangan pelajar tingkatan satu di daerah Tamparuli Sabah - Ritarni, Tokan (2010)
The purpose of this research is to show the effectiveness of formative assessment strategy towards the achievement in geography and mathematics among Form 1 students at SMK Tamparuli, Sabah. This research is also to ensure whether the formative assessment strategy can have an impact towards the students' active involvement in learning. The technique used in this research is a quasi-experiment that involves 84 respondents from two class of musical stream. The respondents are divided into two groups, the control group and the treatment group. The research was conducted for 5 weeks. Data is gathered through questionnaire, interviews as well as pre and post test. Data is analyzed through the use of the t-test. The research shows that there is a significant impact for geography where the difference in student's achievement score for pre and post test in the treatment group as well as between treatment and control group. However the result for mathematics was not significant which means there was no difference in student's achievement score for pre and post test in treatment as well as between treatment and control group. Overall, the majority of students and teachers exposed to the formative assessment strategy accept it in implementation of formative assessment in a positive manner. The implication of this research suggests that the use of formative assessment strategy in classroom is a wise choice in teaching and learning of geography and mathematics to increase student's achievement